2019
DOI: 10.1080/1062936x.2019.1658218
|View full text |Cite
|
Sign up to set email alerts
|

In silico study directed towards identification of the key structural features of GyrB inhibitors targeting MTB DNA gyrase: HQSAR, CoMSIA and molecular dynamics simulations

Abstract: In silico Study Directed Towards Identification the Key Structural Feature of GyrB Inhibitors Targeting MTB DNA Gyrase: HQSAR, CoMSIA and Molecular Dynamics Simulations MTB DNA gyrase subunit B (GyrB) has been identified as promising target for rational drug design against fluoroquinolone drug resistant tuberculosis. In this study, we attempted to identify the key structural feature for highly potent GyrB inhibitors through 2D-QSAR using HQSAR, 3D-QSAR using CoMISA and MD simulations approaches on a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Specifically, Asp79 is highlighted for its ability to form hydrogen bonds with inhibitors. This aligns with the results of Kamsri et al's [35] MD simulation study on GyrB inhibitors of thiadiazole derivatives, which also identified Asn52, Asp79, Arg82, Ile84, and Arg141 as key residues contributing significantly to energy residue and emphasizing their critical role in inhibitor binding. The study conducted by Gl et al [36] identified some novel drug candidates targeting GyrB through drug repurposing.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, Asp79 is highlighted for its ability to form hydrogen bonds with inhibitors. This aligns with the results of Kamsri et al's [35] MD simulation study on GyrB inhibitors of thiadiazole derivatives, which also identified Asn52, Asp79, Arg82, Ile84, and Arg141 as key residues contributing significantly to energy residue and emphasizing their critical role in inhibitor binding. The study conducted by Gl et al [36] identified some novel drug candidates targeting GyrB through drug repurposing.…”
Section: Discussionsupporting
confidence: 89%
“…Benz(e)-azulene-3,8-dione and the reference compound benzamidine showed no cytochrome inhibitory potential. These enzymes are responsible for 90% of drug metabolism as well as interfering with the metabolism of a variety of endogenous substances ( Kamsri et al, 2019 ). This suggests that these compounds would not have restrictions due to the inhibition of these cytochromes and would not be metabolized in the body.…”
Section: Resultsmentioning
confidence: 99%
“…The SMILES codes of the top compounds were generated and used as input files. The results were presented as scores ranging from 0 to 1, where the value 1 corresponds to the most likely target of the query molecule ( Kamsri et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The structure of coumermycin A1 bound to E. coli and Thermus thermophilus GyrB was recently published and provides a path to improved analogues of that natural product class using SBDD . A recent report of quantitative structure–activity relationship (QSAR) studies coupled with molecular dynamics (MD) provided insights into the key structural features and binding interactions of potent mycobacterial GyrB inhibitors . Importantly, this analysis identified structural features that result in both ATPase inhibitory activity and antimycobacterial activity (mycobacterial cell wall permeability).…”
Section: Structure-guided Approaches For Gyrb Inhibitorsmentioning
confidence: 99%
“…42 A recent report of quantitative structure− activity relationship (QSAR) studies coupled with molecular dynamics (MD) provided insights into the key structural features and binding interactions of potent mycobacterial GyrB inhibitors. 43 Importantly, this analysis identified structural features that result in both ATPase inhibitory activity and antimycobacterial activity (mycobacterial cell wall permeability). Novel benzothiazole ureas were proposed based on this evaluation that are predicted to be potent GyrB inhibitors with improved antimycobacterial activity.…”
Section: ■ Targeting Mycobacterial Gyrase Bmentioning
confidence: 99%